Artist management for the music business - Allen, Paul, 1946- (Elsevier/Focal Press, 2007)
Allen prepares you for the realities of successfully directing the careers of talented performers in the high-risk, high-reward music business. You will learn to prepare yourself for a career in artist management - and then learn the tools to coach, lead, organize time, manage finances, market an artist, and carve out a successful career path for both yourself and your clients. The book features profiles of artist managers, an exclusive and detailed template for an artist career plan, and samples of major contract sections for artist management and record deals. Updated information including a directory of artist management companies is available at the book's companion website. A peer reviewer for Artist Management for the Music Business proclaimed ".this is going to be an excellent text. It contains many unique insights and lots of valuable information." This is essential reading for managers, students, and artists in the music business. * Key industry insight for both new and experienced artist managers * Exclusive planning and management tools * Successful career strategies for managers and the artists they manage